The concept of portal system obstruction in Avicenna’s Canon of Medicine - Heydari, Mojtaba (Array, 2018)
Historical literature on portal hypertension is mainly focused on the contemporary advances in therapeutic methods, especially surgical ones. However, it seems that the origin of the human knowledge on the portal system, its association with the caval system, obstructive pathologies in this system and the gastrointestinal bleeding due to hepatic diseases might be much older than previously believed. Avicenna provided a detailed anatomy of the portal venous system and its feeding branches in the Canon of Medicine. Soddat al-Kabed va al-Masarigha (liver and mesenteric occlusion) is also a disease presented by Avicenna with clinical, etiological and therapeutic descriptions suggesting the fact that Soddat al-Kabed va al-Masarigha has multiple similarities with the currently identified concept of “portal hypertension”. He presented sense of heaviness in the liver area with or without mild pain, anemia, pale and inappropriate body color, and loose stool which can be complicated with ascites, infection, fever and abdominal pain as clinical manifestations of this disease. He has also suggested therapeutic approaches including laxative and diuretic herbs to help excreting the obstructive material into stool or urine.